Design and development of an android application “Bus NTU” - Yin, Bangqi. (2013)
Since the past few years, smartphones have been playing increasingly important role in daily life. Much attention has been drawn to development of different applications on smartphone platforms such as Android, IOS etc. “Bus NTU” is an Android application designed specifically for NTU students for their convenience to review NTU bus schedules and positions at any place any time. The application shows user GPS position, map of bus stops and four NTU shuttle bus routes, and current positions and speeds of operating shuttle buses on Google map.